Nilai-nilai Kasus Perceraian di Kampung Tegal Selagalas Kecamatan Sandubaya Kota Mataram - Husnaini, Ninis Husna Januarita; I Wayan Karta; Filsa Era Sativa (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2025)
This study aims to identify the values that contribute to divorce and to examine its impact on children involved in the process. The research employed a descriptive qualitative approach using a case study method, in which the researcher conducted direct fieldwork through observation and in-depth interviews with seven families who had experienced divorce in Kampung Tegal Selagalas, Sandubaya District, Mataram City. The findings reveal that divorce among the respondents was influenced by various value-related factors, with social and economic values being the most dominant. Based on these findings, it can be concluded that maintaining a balance of values within marriage is essential to prevent divorce and that special attention should be given to children affected by it.